(untitled) (Journal of Plant Disease Sciences, 2026)
Rhizoctonia solani Thanatephorus cucumeris in vitro Trichoderma viride in vivo Trichoderma virideKuhn (Teleomorph: (Frank) Donk) is a soil-borne, necrotrophic fungus belonging to the division Basidiomycota Sheath blight is one of the most important and widespread diseases affecting rice in all major rice-growing regions of the world and causes significant reductions in grain yield. In India, rice sheath blight has been reported to cause yield losses of up to 54.3%. Sheath blight management was evaluated through in vitro and in vivo studies using agrochemicals, biologically derived formulations and bioagents. Under conditions, Propiconazole 25% EC (T ) exhibited the highest mycelial growth inhibition (92.95–96.82%), whereas Pyrazosulfuron ethyl 10% WP (T ) was the least effective. Among biologically derived formulations, Beejamrit (T ) showed the highest efficacy, while Agniastra recorded the lowest growth inhibition. In bioagent evaluation, (T ) showed maximum growth inhibition (36.61%), whereas PSF 173 was least effective. Under conditions, Propiconazole 25% EC (T ) resulted in the minimum disease incidence (12.11%), while Pyrazosulfuron ethyl 10% WP showed the highest incidence. Among biologically derived formulations, Beejamrit (T ) recorded the lowest disease incidence (16.62%), whereas Agniastra (T ) showed the highest (26.24%). In bioagent treatments, (T ) effectively reduced disease incidence (18.68%), while PSF 173 (T ) recorded the maximum incidence (22.98%). These results highlight the comparative efficacy of chemical and biological approaches for managing sheath blight disease of rice.